Desain Model Research Based Learning untuk Meningkatkan Budaya Melakukan Riset - Dilla Octavianingrum (Jurnal Pendidikan dan Konseling (JPDK), 2022)
Critical thinking, Creativity, Collaboration, and Communication skills can be trained through educational institutions. One indicator of the success of a university is the culture of doing research. Scientific writing in the form of theses, theses and dissertations is one of the requirements that must be met by undergraduate students, master's programs and doctoral programs as a graduation requirement. The design of the learning model (Research-Based Learning) is needed in the learning process. Research-Based Learning is generally understood as the integration of research in the teaching-learning process. The purpose of this research is to design a learning model to improve students' research skills. The results of this study are composed of Research Based Learning Model Design in the Lesson Planning Course. This draft is feasible to implement with the revised revisions that have been given. The student perceptions are 1) students hope to understand the application of research, 2) make it easier to answer the problem formulation, 3) can improve analytical skills and creativity, 4) can understand the use of theory and practice of learning planning. Keywords: research, planning, learning, design, model